Analysis of the ontogenetic variation in body and beak shape of the Illex argentinus inner shelf spawning groups by geometric morphometrics - Crespi Abril, Augusto Cesar (2010)
In this paper we analysed size and shape differences of body (mantle and fins) and inferior beak of the squid Illex argentinus from two Patagonian inner-shelf spawning groups. A new method was developed to reconstruct three-dimensional coordinates based on the 2-D projection of the beak on a plane. Shape of the beak did not vary between groups, sexes and maturity condition of individuals. Also, no beak shape changes were observed through the ontogeny. In contrast, as larger and heavier squids were considered in shape analysis, body widened near the fin insertion, and fin area increased. Our results suggest that shape adaptations of I. argentinus through the ontogeny reflect modifications to optimize swimming performance rather than to increase gamete holding capacity.